Inhibition of highland barley bran-derived carbon dots on the formation of advanced glycation end products. (15th September 2022) - Zhu, Pei; Zhang, Ying; Xie, Chenchen; Liu, Huilin; Sun, Baoguo
Abstract: Advanced glycation end products (AGEs) are among the series factors that cause the pathology of neurodegenerative diseases. Carbon dots (CDs) with low toxicity, tunable surface chemistry and biocompatibility have been used for biological inhibition and as anticancer agents. In this study, CDs derived from highland barley bran (HBB-CDs) were used to inhibit the formation of AGEs in vitro. The possible inhibitory mechanism was attributed to the decreased number of glycosylation sites in glycosylated β-casein from four and six to three and four in the presence of the HBB-CDs, which was revealed by HPLC–Orbitrap tandem mass spectrometry at the molecular level. Furthermore, the glycosylation degree of each glycosylation site was commanded, and the double saccharification capacity of K167 and K214 was changed. Strong inhibition of AGEs formation in the presence of elevated HBB-CDs suggested that CDs are potential anti-glycation agents and food additives against glycation-associated diseases and food processing. Highlights: Carbon dots derived from highland barley bran (HBB-CDs) were prepared. HBB-CDs were used to inhibit AGEs in vitro . UV absorption and fluorescence spectra showed HBB-CDs inhibited the formation of AGEs. HBB-CDs changed the double saccharification capacity of K167 and K214. HBB-CDs inhibited the process of glycation through reducing the number of glycosylation sites.